Pengaruh Peraturan Menteri Perdagangan (PERMENDAG) Nomor 31 Tahun 2023 terhadap Perkembangan E-commerce di Indonesia - Zahra Afina Mahran; Muhamad Hasan Sebyar (Hakim, 2023)
The rapid development of technology has affected human life in many fields. Along with the rapid development of technology, buying and selling or trading activities have also developed into electronic commerce or better known as e-commerce. The government's awareness of the potential of e-commerce encourages the government to develop relevant laws, along with the rapid development of e-commerce in Indonesia. This scientific research uses normative research methods, which include analyzing problems by processing data obtained from statutory regulations (statute approach) as a research foundation. E-commerce business actors who will provide services using electronic systems must register and apply for a commercial transaction license through electronic systems. One of the main objectives of the government requiring e-commerce players to register with the electronic system is to protect all stakeholders, including economic actors and consumers. Minister of Home Affairs Regulation Number 31 of 2023 is a new regulation issued by the Minister of Trade, Zulkifli Hasan. The regulation is an amendment to Regulation of the Minister of Trade Number 50 of 2020 concerning Regulations on Business Licensing, Advertising, Guidance, and Supervision of Business Entities Trading Through Electronic Systems and aims to support micro, small and medium enterprises (MSMEs) and business entities. While Minister of Home Affairs Regulation Number 31 of 2023 has certain impacts on sellers and buyers, it also provides them with opportunities to improve business operations and protect consumer interests. The TikTok Shop feature is one of the reasons why the Minister of Trade issued the regulation as it does not have an official license to operate as an e-commerce platform. By complying with existing regulations, businesses can capitalize on the opportunities offered by the e-commerce ecosystem and contribute to building a fair and legal digital business environment.